PENDAMPINGAN PEMANFAATAN MEDIA SOSIAL DALAM MENGEMBANGKAN POTENSI EKOWISATA TASIK MERAH DI PULAU RANGSANG PROVINSI RIAU - Chelsy Yesicha; Genny Gustina Sari; Gun Faisal (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
Gemala Sari village, located on the outermost island adjacent to Malaysia and the Indonesian island of Batam, holds a natural and exotic beauty. The challenging condition of access roads to the villages will add to the challenges of the natural tourist adventurers who are currently being loved now. This becomes interesting if the village community independently wants to manage the ecotourism potential while at the same time introducing other potential potentials in the village. The red lake is caused by the red water due to the swampy ground. The red lake is still somewhat closed and has not been touched by the ignorant hands of the community so that the red lake is still maintained its naturalness. Independent community service activities in collaboration with students of the University of Riau develop the natural potential into their thematic programs. The implementation method is in the form of assistance in realizing ecotourism, and the results of the output in the form of promotional videos of Tasik Merah ecotourism are expected to begin to open people's eyes to develop this potential. From the results of the evaluation of assistance, it is very necessary for the participation of extension participants, especially the local government, to be able to manage this potential on their own. The team hopes that this activity can foster their motivation to be selective and active in media. Smart and critical attitude in media that is grown makes them village youths become a virus for their friends who have not participated in tourism promotion. They also hope that the activity can be carried out sustainably, bearing in mind that this is not just education but also entertainment and foster motivation in developing the country by utilizing the potential around them.